Vegetation of the Talabong Mangrove Forest Reserve Suggestions for Rehabilitation - Calumpong, Hilconida P. (Silliman Journal, 2024)
A total of 13 species of mangroves occur in the 200-ha Talabong Forest Reserve. Of these, only Rhizophora spp. occur in substantial stands, the rest consist of just a couple of trees. Immediate multispecies reforestation is critical in the maintenance of diversity in this forest. Establishing the area as a botanical garden may be the only effective long-term management option.